Conocimientos relacionados con aspectos de la administración de medicamentos en la práctica de enfermería en tres hospitales del Atlántico (Colombia) - Sara Caro Ríos; Daniela Díaz Agudelo; Roxana De las Salas Martínez; Esteyci Gutiérrez Cantillo; Cindy Lemus Jimenez; Sarhay Quintero Meléndez (Universidad del Norte, 2014)
Objective: To describe knowledge related to aspects of the administration of medicines into nursing practice. Materials and methods: We conducted a descriptive study from March to May 2011 in three health institutions of Department of Atlántico, which estimated a convenience sample of 104 nurses, who were responsible for carrying out activities related to administration of medicines. We applied two questionnaires, one was answered by nurses in hospitals, and the second was completed by researchers through observation of nursing staff during the administration of medicines. Results: 90.4 % of nurses had knowledge about various adverse drugs reactions that may occur, 53.8 % considered sufficient theory and practice learned in college about pharmacology, 65.4 % reported that timely had the necessary materials in order to administer medication. Conclusions: There are weaknesses in the area of pharmacology knowledge from university training, the availability of hospital materials, in nursing handoff during change of shift and in the spaces for the preparation of medication. A large percentage of nurses know adverse drug reactions, but there is insufficient knowledge about pharmacological terminology such as synergism and antagonism.